Еколого-ценотичні особливості Pulsatilla pratensis (L.) Mill. у Правобережному Лісостепу України - Kuzemko, A.A.; Chekanov, M.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
Coenotic features of the Pulsatilla pratensis (L.) Mill. habitats in the Right-Bank of Forest-Steppe of Ukraine have been identified on the base of the Braun-Blanquet method. It was established that community involving this species belong to 4 associations 3 alliances, 3 orders, and 2 classes with coenotical optimum in communities of the Astragalo austriaci-Salvietum nutantis Korotchenko et Didukh 1997. Environmental assessment of communities by phytoindication method allowed revealing their ecological amplitude, which are within the ecological range of Pulsatilla pratensis. Analyze of communities by participation of species protected on national and international level has shown their high sozological value.